A retrospective analysis investigating the effects of Telazol® and medetomidine on ejaculate characteristics in cheetahs (Acinonyx jubatus) - Baquerizo, Carolina I.; Penfold, Linda M.; Gillis, James D.; Citino, Scott; Marker, Laurie; Crosier, Adrienne E. (Frontiers in Conservation Science, 2023)
Zoo managed cheetahs provide an insurance population for wild cheetahs that are under threat of extinction from habitat loss, lack of prey, competition, pet trade and poaching for skin and bones. Assisted reproductive techniques including artificial insemination, in vitro fertilization, and embryo transfer augment natural breeding programs but rely on good quality semen for best results. It is understood that anesthesia can affect semen characteristics such as ejaculate volume, total sperm count, sperm motility, and incidence of urine contamination. Thus, the aim of this study was to conduct a retrospective analysis of 23 years of data to investigate sperm parameters of semen collected under anesthesia using medetomidine in combination with butorphanol and midazolam or TelazolⓇ alone. Electroejaculation records (Medetomidine, Butorphanol, and Midazolam anesthetized n = 59 ejaculates, from 30 cheetahs, TelazolⓇ anesthetized, n= 169 ejaculates, from 72 cheetahs) were evaluated for incidence of urine contamination. Electroejaculation records (Medetomidine, Butorphanol, and Midazolam anesthetized n = 21 ejaculates, from 17 cheetahs, TelazolⓇ anesthetized, n = 143 ejaculates, from 63 cheetahs) were evaluated for total sperm count, total motility, ejaculate volume, and testicle size. TelazolⓇ treated cheetahs had a numerically higher total sperm count (Median ± SD: 42.58 ± 77.8 × 10 6 spermatozoa) compared to those treated with medetomidine (Median ± SD: 31.2 ± 44.58 × 10 6 spermatozoa), and a significantly (p < 0.05) higher sperm motility (Median ± SD: 70.0 ± 9.71%) compared to medetomidine (Median ± SD: 53.0 ± 16.41%) treated cheetahs. The findings of this study indicate that medetomidine anesthesia results in significantly lower sperm motility and TelazolⓇ anesthesia results in a higher total sperm count and motility, thus resulting in higher quality ejaculate. This information can aid in the veterinary management of the species when involved in genome resource banking and assisted reproductive technologies.